2012
DOI: 10.1038/nature10838
|View full text |Cite
|
Sign up to set email alerts
|

Ancient deuterostome origins of vertebrate brain signalling centres

Abstract: Neuroectodermal signalling centres induce and pattern many novel vertebrate brain structures but are absent, or divergent, in invertebrate chordates. This has led to the hypothesis that signalling centre genetic programs were first assembled in stem vertebrates, which potentially drove morphological innovations. However, this scenario presumes that extant cephalochordates accurately represent ancestral chordate characters, which has not been tested using close chordate outgroups. Here, we report that genetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
319
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(335 citation statements)
references
References 50 publications
14
319
0
2
Order By: Relevance
“…Some phylogenetic analysis using molecular data suggests that are derived and placed within (and not as a sister group of) enteropneusts [97], while others reject this hypothesis completely [98] or are unable to resolve the relationships [99]. In any case, here again in the Hemichordata, we see that the ancestral state for the NS organization is most probably that of a diffuse nerve net (though with extensive internal structure; see, for instance, [86]). This arrangement would also be shared with the echinoderms.…”
Section: Transformation From Nerve Nets To Compact Brains In the Xenamentioning
confidence: 84%
See 1 more Smart Citation
“…Some phylogenetic analysis using molecular data suggests that are derived and placed within (and not as a sister group of) enteropneusts [97], while others reject this hypothesis completely [98] or are unable to resolve the relationships [99]. In any case, here again in the Hemichordata, we see that the ancestral state for the NS organization is most probably that of a diffuse nerve net (though with extensive internal structure; see, for instance, [86]). This arrangement would also be shared with the echinoderms.…”
Section: Transformation From Nerve Nets To Compact Brains In the Xenamentioning
confidence: 84%
“…The reason is that as the centralized NSs of the representatives of these two superphyla are generally organized in different positions and are diverse in their morphology, it is highly contentious to establish possible homologies. Consequently, with the available morphological and molecular data, two main hypotheses exist (that will be further discussed in the next section of the paper): their common ancestor had either a centralized, complex, NS [83] or a diffuse nerve-net [84][85][86]. rstb.royalsocietypublishing.org Phil.…”
Section: Transformation From Nerve Nets To Compact Brains In the Xenamentioning
confidence: 99%
“…By approximately 650 Ma, the bilaterian LCA was more highly tuned for direct interaction with environment and exhibited both anterior/posterior and dorsal/ventral regional patterning and elaboration. Comparative studies strongly suggest that the bilaterian LCA possessed a suite of neurogenic capabilities [51], although the extent of a central nervous system remains a topic of discussion [52]. The capacity for feeding, movement and sensation were well developed.…”
Section: (A) Phasementioning
confidence: 99%
“…Compared with the highly specialized radial form of the body plan of extant echinoderms, hemichordates may retain more of the ancestral form of deuterostomes and are consequently more suitable for comparison as an outgroup taxon 4 . Recent molecular developmental biology studies have shown startling similarities between the molecular architectures of the nervous systems between chordates and non-chordate invertebrates [11][12][13] . Hemichordates and vertebrates share the genetic mechanisms for anteroposterior patterning of the neuroectoderm 11,13 .…”
mentioning
confidence: 99%